Optimal vacuum erectile device therapy regimen for penile rehabilitation in a bilateral cavernous nerve crush rat model. (26th January 2021) - Ma, Ming; Qin, Feng; Wu, Changjing; Xiong, Wenfeng; Yu, Botao; Wei, Shanzun; Huang, Chunxu; Xu, Jianrong; Yang, Xinzong; Yuan, Jiuhong
Abstract: Background: Vacuum erectile device (VED) therapy has been widely used in penile rehabilitation after radical prostatectomy; however, there is no consensus on the best regimen. Objectives: To explore an optimal VED therapy regimen in bilateral cavernous nerve crush (BCNC) rat model. Materials and Methods: Adult male rats were used to measure the effects of different durations (1–30 min) of VED treatment on penile length, penile blood gas analysis, and adverse effects. Forty‐eight adult male rats were randomly divided into Sham, BCNC, and VED treatment groups (2–3–2–3 min, 4–3–3 min, 5–5 min, and 10 min). Penile length, erectile function, and side effects were detected after VED treatment. Histopathological staining and Western blotting were performed to explore the cellular and molecular changes. Results: Prolongation of the duration of VED treatment significantly decreased the penile oxygen saturation, partial oxygen pressure, and arterial blood ratio ( P  < 0.05). Compared with the BCNC group, all VED treatment regimens partially reversed BCNC‐induced penile shortening and erectile dysfunction ( P  < 0.0001), with the 4–3–3‐min and 5–5‐min treatment groups exhibiting more significant improvement than the 10‐min and 2–3–2–3‐min treatment groups ( P  < 0.0001). The mechanism may be related to the up‐regulation of the smooth muscle cell/collagen ratio, endothelial nitric oxide synthase, and α‐smooth muscle actin (all P  < 0.0001); and the down‐regulation of hypoxia‐inducible factor‐1α, transforming growth factor‐β1, and apoptosis (all P  < 0.0001). The incidence of adverse effects in the 2–3–2–3‐min treatment group was the highest. Discussion: The commonly used VED therapy regimens maintained erectile function and penile length of BCNC rat by relieving hypoxia and fibrosis, and no further benefits were observed with increased treatment frequency or prolonged treatment duration. Conclusion: Two consecutive 5‐min treatments with a short interval is the optimal VED therapy regimen for penile rehabilitation in BCNC rat model.